Objective Scoring Outcome Analysis of Redo Urethroplasty for Failed Hypospadias (TAJ: Journal of Teachers Association, 2019)
Background: Failed hypospadias refers to any hypospadias repair that leads to complicationsor causes patient dissatisfaction. One of the commonest major complications of hypospadias surgery is urethrocutaneous fistula.Objectives: Present study aimed to determine a better procedure of salvage urethroplasty for failed hypospadias, caused by persistentlarge (>4mm) or multiple -small (